Guest Editorial: The Gig Economy and Women Workers in the Middle East - Stella Morgana (Global Labour Journal)
What is the impact of the so-called gig economy on women workers in the Middle East? Does digitalisation represent a catalyst for female labour participation in the region or a burden leading to further financial insecurity and invisibility? How are ordinary women gig workers re-imagining their tech lives and challenging unwritten rules, patriarchy and lack of access to the labour market? Featuring articles analysing case studies in Egypt, Iraq, Oman and the United Arab Emirates, this special issue addresses the abovementioned questions, directly speaking to the academic debate on the global gig economies. Proving a regional and local perspective, it contributes to a more plural understanding of gig work in a multiplicity of contexts, practices and experiences. It investigates the relationship between the daily and the digital to explore the role of platforms in shaping female labour participation and women’s empowerment, as well as issues of precarisation and marginalisation. By proposing a collection of original and pioneering research on an understudied topic as applied to specific contexts in the Middle East, the special issue broadens the analysis of the so-called gig economy beyond a mere economic lens, bringing together multi-disciplinary insights and approaches from sociology, political economy and digital anthropology. It shows that online gig work is neither a crystallised nor monolithic dimension. Instead, platforms - in some instances - have become vectors of formalisation instead of leading only to informality, such as in the case of taxi driving app and home cooking/food delivery, where apps have enhanced more regulation as formality was not the norm before. Women gig workers are re-imagining their roles in their everyday practices of working from home, blurring the lines between the public and the private spheres. They adapt to neoliberal conditions of flexibilisation to sustain their needs in contexts where processes of labour informalisation have long permeated the development of labour relations.